Randomized controlled trial on the effectiveness of web-based Genomics Nursing Education Intervention for undergraduate nursing students: a study protocol - Dumo, Anndra Margareth; Laing, Bobbi; Lim, Anecita Gigi; Palaganas, Erlinda; Abad, Peter James; Valdehueza, Ofelia; Palovaara, Marjo; Saunders, Hannele; Estola, Matti; Mandysová, Petra; Maguire, Jane; Ward, Linda D; et al. (Wiley-Blackwell, 2020)
Aim: To describe a randomized controlled trial protocol that will evaluate the effectiveness of two web-based genomic nursing education interventions. Background: Preparing future nurses to be competent in genetic and genomic concepts is fundamental to ensure appropriate clinical application. However, genetics–genomics concepts are still new in the field of nursing. Little is known about what type and kind of web-based nursing education is effective in improving the knowledge of nursing students. To address these knowledge gaps, a web-based ‘Genomic Nursing Education Intervention’ will be developed and compared with an existing online education programme. Design: A randomized controlled trial of two groups with pre-test and repeated posttesting. Methods: The Genomic Nursing Concept Inventory, a validated tool, will be used to assess the genetics–genomics knowledge of nursing students. Participants will be randomly allocated to either a control or an intervention group. The control group will receive the standard web-based nursing education, while the intervention group will receive a newly developed web-based education intervention. Outcome measures include the students’ knowledge level of nursing genetics–genomics concepts. Participants will be retested at 3 and 6 months. Conclusion: Current evidence shows that ensuring nurses have adequate education in genetic–genomic concepts is challenging. This study will demonstrate which of two web-based nursing education methods is more effective in teaching genetic–genomic concepts. This research project will better prepare the nursing profession in their careers for the emerging advance technologies in genetics–genomics and personalized health care. Impact: Current evidence shows major challenges in ensuring that nurses have adequate education in genetics–genomics concepts. Less is known about what approaches to web-based education are effective to improve the knowledge gaps of nursing students in genetics–genomics concepts. This study will determine which type of web-based nursing education is effective in improving the genetics–genomics knowledge of nursing students. This research project will help better prepare nurses in dealing with advances in genetics–genomics in their careers.
Randomizovaná kontrolovaná studie týkající se efektivnosti internetové intervence Genomics Nursing Education pro studenty v bakalářském programu ošetřovatelství: protokol studie
Keywords: education; genetics; genomics; midwives; nurses; nursing; edukace; genetika; genomika; porodní asistentky; sestry; ošetřovatelství